World Total Factor Productivity Growth and the Steady-State Rate in the 20th Century (2013)
I estimate a Solow model augmented with human capital in 42 countries for 1910-2000. Estimated TFP growth is 0.3%/year, and the steady-state rate for GDP/capita is 1.0%/year. Implicitly for high-income countries maintaining growth above this rate will be increasingly difficult.